The Habituation Approach of Memorising Short Al-Qur’an Letters and Their Daily Practice in Elementary School Students - Siti Nurkhayati; Sutrisno Sutrisno (JENIUS (Journal of Education Policy and Elementary Education Issues), 2022)
The background of this research is that memorising the Al-Qur’an, especially the short letters Juz 30, is increasingly being applied in Islamic educational institutions. However, phenomena in the field are still found to be low enthusiasm for memorising short surahs in the Al-Qur’an and the lack of practising the Al-Qur’an in students’ daily lives, such as the misalignment of what students say and do, including at MI Muhammadiyah Ngadirejo. Therefore, a teacher needs to be able to choose and use the right approach to improve the memorisation of short surahs in the Al-Qur’an and practice them in everyday life. The aims of this study were (1) to find out how important the approach to memorising short surahs in the Al-Qur’an is essential and its practice in daily life, (2) to find the implementation of the habituation approach by memorising short surahs and their practice in daily life, (3) found the results of the habituation approach by memorising short letters and practising them in everyday life. The type of research is field research. Collecting data through observation, interviews and documentation. The results of this study are that students can be more confident in practising the contents of the Al-Qur’an, as seen from student behaviour and student recognition that their hearts become calmer, besides that students memorise and read short letters more smoothly